ADAPTASI EKOFISIOLOGI TERHADAP IKLIM TROPIS KERING: STUDI ANATOMI DAUN SEPULUH JENIS TUMBUHAN BERKAYU - Rindyastuti, Ridesti; Hapsari, Lia (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTStudy on foliar anatomic structure of tropical plants are useful to study various aspects of plant life related to photosynthetic, productivity, carbon sequestration, adaptation to environmental stresses as the results of global climate change, etc. This study was conducted to investigate foliar anatomic structure of ten tropical woody plant species including Barringtonia asiatica, Dracontomelon dao, Heritiera littoralis, Diospyros discolor, Calophyllum inophyllum, Antidesma bunius, Schleichera oleosa, Syzygium cumini, Madhuca longifolia dan Adenanthera pavonina; also to discuss its implication to ecophysiological adaptation to tropical dry climate. The results showed that ten woody plant species studied had variation of adaptation pattern to dry tropical climate, exposure to high light intensity or open shade and photosynthesis activity. Plant species in Group II (Antidesma bunius, Madhuca longifolia and Adenanthera pavonina) has relatively higher adaptation compared to Group I (Diospyros discolor, Calophylum inophyllum, Dracontomelon dao, Schleichera oleosa, Heritiera littoralis, Baringtonia asiatica and Syzygium cumini). Some foliar anatomic structures including palisade shape and size, stomatal index, stomatal density, spongy mesophyll thickness, the ratio of P/T and P/S are important characters that can be used as indicator of changes in environmental factors; particularly the density of stomata as indicators of climate change in dry tropic area.Keywords: adaptation, dry climate, eco-physiology, foliar anatomy, woody plant